Hubungan Fatigue dengan Kualitas Tiudr Pasien Kanker Payudara Stadium Lanjut yang Menjalani Kemoterapi di RSUD Arifin Achmad - Nurliana; Nurul Huda; Rismadefi Woferst (Jurnal SMART Keperawatan, 2025)
Introduction: Breast cancer is the most common type of cancer that occurs in women due to the growth of abnormal cells in the breast tissue. One of the most widely used treatments is chemotherapy with the most common side effect being fatigue. Continuous fatigue can affect the patient's sleep quality, especially in advanced stages. Objective: This study aims to determine the relationship between fatigue and sleep quality of advanced breast cancer patients undergoing chemotherapy. Method: This study used a descriptive correlation design with a cross-sectional approach. This study amounted to 43 respondents who were taken based on the inclusion criteria using the total sampling technique. The instruments used the study were Brief Fatigue Inventoy (BFI) and Pittsburgh Sleep Quality Index (PSQI). The analysis used was Chi Square test. Results: As many as 21 respondents had fatigue in the mild category (48,8%) and 22 respondents had fatigue in the severe category (51,2%) while in the sleep quality of 43 respondents, 8 respondents had good sleep quality (18,6%) and 35 respondents had poor sleep quality (81,4%). There is no significant relationship between fatigue and sleep quality in advanced breast cancer patients undergoing chemotherapy with p value (0,689) > alpha (0,05). Conclusion: Fatigue has no significant relationship with sleep quality in advanced breast cancer patients undergoing chemotherapy. Can further develop the results of this study regarding other factors such as physical, psychological